2007
DOI: 10.1248/cpb.55.1748
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Fatty Acid from Pleurocybella porrigens

Abstract: The fungus Pleurocybella porrigens (called 'sugihiratake' in Japanese), which is a basidiomycete of the Trichoromataceae family, is a lignicolous agaric mushroom that produces pure white, relatively small pleurotoid fruiting bodies on rotting conifers, often in abundance.1) This edible mushroom grows during the late summer and autumn and is native to all districts of Japan, including the Tohoku and Hokuriku areas. P. porrigens was suspected to cause acute encephalopathy including coma and spasm in the Tohoku a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 5 publications
(5 reference statements)
0
16
0
Order By: Relevance
“…A cytotoxic fatty acid (IC 50 =46.5  μ g/ml in B16F1 cells) and unusual amino acids (toxicity in glial cells at several tens of μ g/ml) have been isolated from these mushrooms by other groups. 28, 29, 30 Although, many researchers tried to find a causative substance related to the encephalopathy, no evidence has been found so far. In addition, ESA-mediated apoptosis appears to be a novel type of ERK1/2- and RIP1-dependent cell death.…”
mentioning
confidence: 99%
“…A cytotoxic fatty acid (IC 50 =46.5  μ g/ml in B16F1 cells) and unusual amino acids (toxicity in glial cells at several tens of μ g/ml) have been isolated from these mushrooms by other groups. 28, 29, 30 Although, many researchers tried to find a causative substance related to the encephalopathy, no evidence has been found so far. In addition, ESA-mediated apoptosis appears to be a novel type of ERK1/2- and RIP1-dependent cell death.…”
mentioning
confidence: 99%
“…Therefore, compounds 1 / 2 were characterized as methyl (10 E ,12 E )-14-hydroxy-9-oxo-10,12-octadecadienoate. Further spectroscopic analyses revealed that compared with the reported (–)-enantiomer of compound 10 (porrigenic acid) [ 12 ], 1 / 2 were neither active enough in the [ α ] D measurement, nor showed decent Cotton effect in the ECD experiment; this alerted us of its racemic or scalemic nature. Subsequent chiral high performance liquid chromatography (HPLC) analysis clearly revealed a pair of enantiomers in a ratio of ca.…”
Section: Resultsmentioning
confidence: 99%
“…Other putative causative toxins for angel's wing mushroom-induced encephalopathy Apart from our hypothesis described above, many scientists have proposed various compounds as causative toxin(s) for the encephalopathy, such as vitamin D analogues [44], a fatty acid [45], oligosaccharides [46] and cytotoxic amino acids [47]. In spite of the presence of many causative toxin candidates, many more studies are required to finally identify the causative toxin(s) in the angel's wing mushroom.…”
Section: Separation Columnmentioning
confidence: 94%